2017
DOI: 10.1002/cpe.4352
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the number of response time service level objective violations by a cloud‐HPC convergence scheduler

Abstract: Summary Job scheduling is an old topic in High‐Performance Computing (HPC), and it is more and more studied in data centers. Large data centers are often split into separate partitions for cloud computing and HPC; each partition normally has its specific scheduler. The possibility of migrating jobs from the HPC partition to the cloud one is a topic widely discussed in the literature. However, job migration from cloud to HPC is a much less explored topic. Nevertheless, such migration may be useful in many situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, the paper neither takes into account the HPC workload nor discusses the issues of cross-application interference. Kraemer et al [19] developed a job migration mechanism for transferring jobs from the cloud environment to the high-performance computing environment. The primary goal is to reduce the amount of response time violations associated with cloud jobs while not interfering with the execution of HPC jobs.…”
Section: Related Workmentioning
confidence: 99%
“…However, the paper neither takes into account the HPC workload nor discusses the issues of cross-application interference. Kraemer et al [19] developed a job migration mechanism for transferring jobs from the cloud environment to the high-performance computing environment. The primary goal is to reduce the amount of response time violations associated with cloud jobs while not interfering with the execution of HPC jobs.…”
Section: Related Workmentioning
confidence: 99%
“…Apart from them, some other researchers put forward resource allocation algorithms based on cost or profit. 38 However, these methods mainly solve the problems of assigning tasks to VMs or allocating VMs to hosts. The former mode tries to determine VMs on which the applications will be executed before the application deployment according to the resource usage in a period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In parallel applications, batch scheduling was often adopted to organize the execution parallel application. 38 However, these methods mainly solve the problems of assigning tasks to VMs or allocating VMs to hosts. The precondition of these approaches is that an application can be completed by a single VM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results also showed that the selected value should be above a particular threshold as unnecessary frequent checkpointing may lead to performance degradation. Kraemer et al, in their article “ Reducing the number of response time Service Level Objective violations by a cloud‐HPC convergence scheduler ,” introduced a scheduling strategy for migrating jobs from the cloud environment to the HPC environment. The main aim is to reduce the number of response time violations of cloud jobs without interfering with HPC job execution.…”
Section: Themes Of This Special Issuementioning
confidence: 99%